An evaluation of faculty participation in the selection program of the Instructional Media Unit of Elizabeth Seton School - Dela Vega, Magana A. (2009)
The study determined the extent and degree of participation of faculty personnel of the Elizabeth Seton School in the selection of print and non-print materials of the Instructional Media Unit (IMU). It also analyzed the different factors that affect and influence faculty and librarians in the selection process.